Gamma Radiation Sterilization Reduces the High-cycle Fatigue Life of Allograft Bone - Islam, Anowarul (Clin Orthop Relat Res, 2015)
BACKGROUND: Sterilization by gamma radiation impairs the mechanical properties of bone allografts. Previous work related to radiation-induced embrittlement of bone tissue has been limited mostly to monotonic testing which does not necessarily predict the high-cycle fatigue life of allografts in vivo. QUESTIONS/PURPOSES: We designed a custom rotating-bending fatigue device to answer the following questions: (1) Does gamma radiation sterilization affect the high-cycle fatigue behavior of cortical bone; and (2) how does the fatigue life change with cyclic stress level? METHODS: The high-cycle fatigue behavior of human cortical bone specimens was examined at stress levels related to physiologic levels using a custom-designed rotating-bending fatigue device. Test specimens were distributed among two treatment groups (n = 6/group); control and irradiated. Samples were tested until failure at stress levels of 25, 35, and 45 MPa. RESULTS: At 25 MPa, 83% of control samples survived 30 million cycles (run-out) whereas 83% of irradiated samples survived only 0.5 million cycles. At 35 MPa, irradiated samples showed an approximately 19-fold reduction in fatigue life compared with control samples (12.2 × 10(6) ± 12.3 × 10(6) versus 6.38 × 10(5) ± 6.81 × 10(5); p = 0.046), and in the case of 45 MPa, this reduction was approximately 17.5-fold (7.31 × 10(5) ± 6.39 × 10(5) versus 4.17 × 10(4) ± 1.91 × 10(4); p = 0.025). Equations to estimate high-cycle fatigue life of irradiated and control cortical bone allograft at a certain stress level were derived. CONCLUSIONS: Gamma radiation sterilization severely impairs the high cycle fatigue life of structural allograft bone tissues, more so than the decline that has been reported for monotonic mechanical properties. Therefore, clinicians need to be conservative in the expectation of the fatigue life of structural allograft bone tissues. Methods to preserve the fatigue strength of nonirradiated allograft bone tissue are needed. CLINICAL RELEVANCE: As opposed to what monotonic tests might suggest, the cyclic fatigue life of radiation-sterilized structural allografts is likely severely compromised relative to the nonirradiated condition and therefore should be taken into consideration. Methods to reduce the effect of irradiation or to recover structural allograft bone tissue fatigue strength are important to pursue.